2019
DOI: 10.15446/dyna.v86n211.80864
|View full text |Cite
|
Sign up to set email alerts
|

Metrópolis: un juego serio emergente en una ciudad inteligente

Abstract: Emerging serious games mark the beginning of a new era in video games. Emerging serious games introduce advances in distributed artificial intelligence into their design in order to guide the player’s manipulation of a specific subject in an adaptive way. In this article, we present a city simulator game, called Metropolis, which generates emergent properties. Metropolis can be used by a smart city for city planning, to make collective decisions, and for other purposes. This paper describes why Metropolis can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Serious digital games, due to their immersive and engagement potential, have been used in several domains as tools to promote engagement and learning [35][36][37]. The use of these games is also discussed as a social innovation strategy [8,38] and gamification is often used as an alternative to encourage citizen collaboration to improve public services [7,[9][10][11]. This research work is grounded on the idea that serious games can also be thought of as tools for understanding public service delivery processes, enabling citizens to understand the context, difficulties, particularities, challenges, and characteristics of these processes [12].…”
Section: Business Process-based Digital Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious digital games, due to their immersive and engagement potential, have been used in several domains as tools to promote engagement and learning [35][36][37]. The use of these games is also discussed as a social innovation strategy [8,38] and gamification is often used as an alternative to encourage citizen collaboration to improve public services [7,[9][10][11]. This research work is grounded on the idea that serious games can also be thought of as tools for understanding public service delivery processes, enabling citizens to understand the context, difficulties, particularities, challenges, and characteristics of these processes [12].…”
Section: Business Process-based Digital Gamesmentioning
confidence: 99%
“…Among the initiatives to shorten the distance between citizens and public services, there are those exploring digital games, assuming that digital games can strengthen democracy and civic participation through social engagement [7][8][9][10][11]. Previous research has demonstrated the feasibility of building digital games from public services' process models.…”
Section: Introductionmentioning
confidence: 99%
“…Jogos Baseados em Processos de Prestac ¸ão de Servic ¸os Públicos Os jogos digitais sérios, devido ao seu potencial de imersão e engajamento, têm sido utilizados em diversos domínios como ferramentas para promover o engajamento e a aprendizagem [10]- [12]. O uso de jogos digitais sérios também é discutido como uma estratégia de inovac ¸ão social [13] [14] e a gamificac ¸ão é frequentemente usada como uma alternativa para incentivar a colaborac ¸ão do cidadão para melhorar os servic ¸os públicos [15] [3] [4] [16]. Este trabalho de pesquisa está fundamentado na ideia de que os jogos sérios também podem ser pensados como ferramentas para a compreensão dos processos de prestac ¸ão de servic ¸os públicos, possibilitando aos cidadãos compreender o contexto, as dificuldades, particularidades, desafios e características desses processos [5].…”
Section: Conceitos Fundamentaisunclassified